PENINGKATAN KAPASITAS STUDI KELAYAKAN BISNIS PADA BUMDES DAN UMKM DI SUNGAI LANGKA KABUPATEN PESAWARAN - Muslimin; Sri Hasnawati; Nindya Puspitasari Dalimunthe; Rialdi Azhar (Jurnal Abdimas Bina Bangsa, 2021)
The aim of this paper to describe how to enhance technical skill of Bumdes and SMEs in developing business financial feasibility analysis. Specifically, this activity aims to identify local economic potentials as a foundation to foster SME’s growth by facilitating developing financial plan of their business. Participatory approach is used to transfer of knowledge of the training. As the pandemic situation, social media is used to account skill required. By using pre and post test to evaluate the training, the results show that the participants need to continuous training to apply the steps of feasibility study analysis. Even there is a progress in developing the materials technically, the score is still lower to transform the aspect financially. Financial literate dissemination is still needed to enhance financial skills of the participants.